On Convergence of Multigrid Method for Nonnegative Definite Systems (Journal of Computational Mathematics, 2005)
In this paper, we consider multigrid methods for solving symmetric nonnegative definite matrix equations. We present some interesting features of the multigrid method and prove that the method is convergent in $ L_2 $ space and the convergent solution is unique for such nonnegative definite system and given initial guess.
Keywords: Multigrid; Singular Problem; Convergence.